Treating cancer through modulating exosomal protein loading and function: The prospects of natural products and traditional Chinese medicine - Lulu Meng; Chao Zhang; Pei Yu (Elsevier, 2024)
Exosomes, small yet vital extracellular vesicles, play an integral role in intercellular communication. They transport critical components, such as proteins, lipid bilayers, DNA, RNA, and glycans, to target cells. These vesicles are crucial in modulating the extracellular matrix and orchestrating signal transduction processes. In oncology, exosomes are pivotal in tumor growth, metastasis, drug resistance, and immune modulation within the tumor microenvironment. Exosomal proteins, noted for their stability and specificity, have garnered widespread attention. This review delves into the mechanisms of exosomal protein loading and their impact on tumor development, with a focus on the regulatory effects of natural products and traditional Chinese medicine on exosomal protein loading and function. These insights not only offer new strategies and methodologies for cancer treatment but also provide scientific bases and directions for future clinical applications.